EDUKASI PRINSIP GIZI SEIMBANG DAN PENGUKURAN LILA PADA IBU HAMIL - Sari, Anjelina Puspita; Silaban, Titin Dewi Sartika; Romlah, Romlah; Hardika, Bangun Dwi (Universitas Muhammadiyah Mataram, 2025)
Abstrak: Jumlah ibu hamil yang mengalami KEK di Provinsi Sumatera Selatan juga tergolong tinggi, dengan total 8.512 ibu hamil yang terindikasi KEK pada tahun 2023. Status gizi kurang berkaitan dengan kemungkinan komplikasi yang dapat terjadi jika ibu tidak menerapkan prinsip gizi seimbang. Tujuan dari pengabdian ini adalah meningkatkan kemampuan soft skill dari edukasi yang diberikan sehingga ibu lebih peduli terhadap pemenuhan nutrisi selama kehamilannya. Metode pengabdian dengan memberikan ibu edukasi mengenai gizi seimbang selama kehamilan di Praktik Mandiri Bidan Lismarini dengan sasaran sebanyak 20 orang ibu hamil trimester 1,2 dan 3, namun sebelumnya ibu diberikan soal pretest dan dilakukan posttest setelahnya. Hasil yang telah dicapai terbukti adanya peningkatan pengetahuan pada ibu hamil dimana nilai pretest didapatkan rata-rata nilai 50, dan setelah dilakukan post tes terjadi peningkatan nilai rata-rata menjadi 85.Abstract: The number of pregnant women experiencing malnutrition in South Sumatra Province is also relatively high, with a total of 8,512 pregnant women who are indicated to have undernourished status in 2023. Nutritional status is less related to the possibility of complications that can occur if the mother does not apply the principle of balanced nutrition. The purpose of this service is to improve the soft skills of the education provided so that mothers are more concerned about the fulfillment of nutrition during their pregnancy. The service method by providing mothers education about balanced nutrition during pregnancy at the Lismarini Midwife Independent Practice with a target of 20 pregnant women in the 1st, 2nd and 3rd trimester, but previously the mother was given pre-test questions and a post test was carried out afterwards. The results that have been achieved are proven to be an increase in knowledge in pregnant women where the pretest score is obtained with an average value of 50, and after the post test is carried out there is an increase in the average score to 85.